Clinical evaluation in periodontitis patient after curettage - Widowati Witjaksono; Roselinda Abusamah; TP. Kannan (Dental Journal (Majalah Kedokteran Gigi), 2006)
Curettage is used in periodontics to scrap off the gingival wall of a periodontal pocket, and is needed to reduce loss of attachment (LOA) by developing new connective tissue attachment in patients with periodontitis. The purpose of this study was to evaluate the success of curettage by the formation of tissue attachment. This clinical experiment was done by comparing LOA before curettage, 2 weeks and 3 weeks after curettage on 30 teeth with the indication of curettage. Study population were periodontitis patient who attending dental clinic at Hospital University Science Malaysia (HUSM) with inclusion criteria good general health condition, 18 to 55 years old male or female and presented with pocket depth > 3mm. The teeth were thoroughly scaling before intervention and evaluated by measuring the periodontal attachment before curettage, two weeks and three weeks after curettage. Repeated measure ANOVA and Paired T Test were used to analyze the data. The result of the study showed that there was reduction in the periodontal attachment loss in periodontitis patient after curettage either in the anterior or posterior teeth which were supported by statistical analysis. This study concluded that curettage could make reattachment of the tissue